How Common—and How Serious— Is Clostridium difficile Colitis After Geriatric Hip Fracture? Findings from the NSQIP Dataset. Issue 3 (March 2018) - Bovonratwet, Patawut; Bohl, Daniel D.; Russo, Glenn S.; Ondeck, Nathaniel T.; Nam, Denis; Della Valle, Craig J.; Grauer, Jonathan N.
Abstract: Background: Patients with geriatric hip fractures may be at increased risk for postoperative Clostridium difficile colitis, which can cause severe morbidity and can influence hospital quality metrics. However, to our knowledge, no large database study has calculated the incidence of, factors associated with, and effect of C. difficile colitis on geriatric patients undergoing hip fracture surgery. Questions/Purposes: To use a large national database with in-hospital and postdischarge data (National Surgical Quality Improvement Program ® [NSQIP®]) to (1) determine the incidence and timing of C. difficile colitis in geriatric patients who underwent surgery for hip fracture, (2) identify preoperative and postoperative factors associated with the development of C. difficile colitis in these patients, and (3) test for an association between C. difficile colitis and postoperative length of stay, 30-day readmission, and 30-day mortality. Patients and Methods: This is a retrospective study. Patients who were 65 years or older who underwent hip fracture surgery were identified in the 2015 NSQIP database. The primary outcome was a diagnosis of C. difficile colitis during the 30-day postoperative period. Preoperative and procedural factors were tested for association with the development of C. difficile colitis through a backward stepwise multivariate model. Perioperative antibiotic type and duration were not included in the model, as this information was not recorded in the NSQIP. The association between C. difficile colitis and postoperative length of stay, 30-day readmission, and 30-day mortality were tested through multivariate regressions, which adjusted for preoperative and procedural characteristics such as age, comorbidities, and surgical procedure. A total of 6928 patients who were 65 years or older and underwent hip fracture surgery were identified. Results: The incidence of postoperative C. difficile colitis was 1.05% (95% CI, 0.81%-1.29%; 73 of 6928 patients). Of patients who had C. difficile colitis develop, 64% (47 of 73 patients) were diagnosed postdischarge and 79% (58 of 73 patients) did not have a preceding infectious diagnosis. Preoperative factors identifiable before surgery that were associated with the development of C. difficile colitis included admission from any type of chronic care facility (versus admitted from home; relative risk [RR] = 1.98; 95% CI, 1.11-3.55; p = 0.027), current smoker within 1 year (RR = 1.95; 95% CI, 1.03-3.69; p = 0.041), and preoperative anemia (RR = 1.76; 95% CI, 1.07-2.92; p = 0.027). Patients who had pneumonia (RR = 2.58; 95% CI, 1.20-5.53; p = 0.015), sepsis (RR = 4.20; 95% CI, 1.27-13.82; p = 0.018), or "any infection" (RR = 2.26; 95% CI, 1.26-4.03; p = 0.006) develop after hip fracture were more likely to have C. difficile colitis develop. Development of C. difficile colitis was associated with greater postoperative length of stay (22 versus 5 days; p < 0.001), 30-day readmission (RR = 3.41; 95% CI, 2.17-5.36; p < 0.001), and 30-day mortality (15% [11 of 73 patients] versus 6% [439 of 6855 patients]; RR = 2.16; 95% CI, 1.22-3.80; p = 0.008). Conclusions: C. difficile colitis is a serious infection after hip fracture surgery in geriatric patients that is associated with 15% mortality. Patients at high risk, such as those admitted from any type of chronic care facility, those who had preoperative anemia, and current smokers within 1 year, should be targeted with preventative measures. From previous studies, these measures include enforcing strict hand hygiene with soap and water (not alcohol sanitizers) if a provider is caring for patients at high risk and those who are C. difficile -positive. Further, other studies have shown that certain antibiotics, such as fluoroquinolones and cephalosporins, can predispose patients to C. difficile colitis. These medications perhaps should be avoided when prescribing prophylactic antibiotics or managing infections in patients at high risk. Future prospective studies should aim to determine the best prophylactic antibiotic regimens, probiotic formula, and discharge timing that minimize postoperative C. difficile colitis in patients with hip fractures. Level of Evidence: Level III, therapeutic study.